(untitled) (Asian-Australasian Journal of Food Safety and Security, 2017)
The experiment was carried out at Kaunia upazila in Rangpur district to investigate the socio-economic conditions of the farmers, use of different hormones, feed additives and their effects. The data were collected through interview schedule by selecting 30 respondents who were involved in goat fattening. Collected data were analyzed using Excel sheet. It was found that most of the farmers were middle aged categories (50%) and educational level of the farmers was primary (57%), secondary (23%), and higher secondary (10%). Half of the respondents were farmer, followed by businessman (20%). About 67% farmers used own capital, 3% farmers took loan from bank and 23% took loan from other sources such as NGO. It was also found that about 33% respondents had on short time training experience and the rest 67% had no experience. Almost 97% farmers reared Black Bengal goat and 3% Jamunapari goat. Near about 97% farmers used roadside grass and tree leaves and only 3% farmers used cultivated fodder. Only 7% farmer used growth promoter & feed additives in feed where 93% farmers are not being used growth promoter &feed additives in feed. But not a single farmer used growth hormones for fattening purpose. Therefore, still now goat meat would be safe for human consumption without any health hazard. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 1-6